2019
DOI: 10.1038/s41598-019-41679-z
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive correlates of abnormal myelination in psychosis

Abstract: Psychotic illness has consistently been associated with deficits in cognitive function and reduced white matter integrity in the brain. However, the link between white matter disruptions and deficits in cognitive domains remains poorly understood. We assessed cognitive performance and white matter myelin water fraction (MWF) using multicomponent driven equilibrium single pulse observation of T1 and T2 (mcDESPOT) in recent-onset psychosis patients and age-matched healthy controls (HC). Psychosis patients showed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 61 publications
(62 reference statements)
0
10
0
Order By: Relevance
“…Furthermore, psychotic symptoms are related to functional connectivity alterations in the frontostriatal, frontotemporal, and frontoparietal circuits[ 132 ]. The frontostriatal circuit comprises the connections between the PFC and basal ganglia[ 128 ].…”
Section: Evidence Of Wm Alterations In Schizophrenia and Bipolar Diso...mentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, psychotic symptoms are related to functional connectivity alterations in the frontostriatal, frontotemporal, and frontoparietal circuits[ 132 ]. The frontostriatal circuit comprises the connections between the PFC and basal ganglia[ 128 ].…”
Section: Evidence Of Wm Alterations In Schizophrenia and Bipolar Diso...mentioning
confidence: 99%
“…Patients with schizophrenia have compromised fornix integrity and disrupted functional connectivity between the PFC and the hippocampus[ 138 , 139 ]. Further analysis of functional connectivity has provided evidence of alterations in the frontostriatal and frontoparietal circuits that are also related to cognitive dysfunctions in schizophrenia subjects[ 132 ].…”
Section: Evidence Of Wm Alterations In Schizophrenia and Bipolar Diso...mentioning
confidence: 99%
“…Myelin underpins the efficiency and speed of neuronal signal conduction, enabling rapid communication between disparate brain regions and efficient functional integration during cognitive processing. White matter changes linked to myelin are associated with cognitive function both in health (Lu et al, ; Mabbott, Noseworthy, Bouffet, Laughlin, & Rockel, ; Nagy, Westerberg, & Klingberg, ) and pathology (Vanes et al, ; Vanes, Mouchlianitis, Wood, & Shergill, ). Individual differences in white matter myelination may thus be a general risk factor for or an outcome of psychiatric disorders (Fields, ).…”
Section: Introductionmentioning
confidence: 99%
“…This is consistent with the present data where changes in the paw angle of the forelimb and hindlimb in the scrambled treated stroke group were also associated with a reduced volume of myelinated tracts in the ischemic hemisphere. White matter pathways are critical for cognitive functions (Fields, 2008 ; Chevalier et al, 2015 ; Vanes et al, 2019 ). Studies have suggested myelin breakdown occurs as a consequence of stroke and due to chronological aging (Guttmann et al, 1998 ; Peters et al, 2000 ; Bartzokis et al, 2001 ).…”
Section: Discussionmentioning
confidence: 99%